Traffic Accidents Analysis on Dry and Wet Road Bends Surfaces in Greater Manchester-UK - Ismael, Karzan S.; Razzaq, Noorance A. (Kurdistan Journal of Applied Research, 2017)
Road accidents becomes global health and safety issues because of the gradual increase in the number of injuries and fatalities. In the UK, road accidents due to weather conditions has been one of the traffic safety challenges for researchers as well as drivers particularly in Greater Manchester. This is because of its influence on driver behaviour approaching traffic lights on the road bends. Hence, to better understand driver behaviour, this paper presents various driving behaviour on wet and dry road conditions. Data were obtained from police reports of road accidents at hazardous locations in Greater Manchester between 2011 and 2015. The reported data covers information regarding: Accidents, Vehicle, and Casualties. The obtained data was used to examine how road surface is associated with road accidents by using Chi-Square statistical test. The analysis showed that road surface significantly contributed to accidents at bend roads. Moreover, drivers’ behaviour was investigated as they can be expected to have a significant impact on accident occurrence. Finally, the main goal is that these results might reflect the safety issue at bend roads.